(untitled) (Palíndromo, 2021)
This text is an interview with the teacher and visual artist Andréa Stanislav. First, she speaks about the beginning of her career in Visual Arts, the schools she attended, the artists she had classes with and her interest in photography, installation and performances. After commenting on her work as a teacher in an institution that has an interdisciplinary path, she talks a little about the challenges of teaching sculpture classes using digital platforms. In the end, she sends some images of the current work, related to the pandemic context.